Evaluation of shear lag effect in HSS-UHPC composite beams with perfobond strip connectors: Experimental and numerical studies. (July 2022) - He, Shaohua; Yang, Gang; Zhou, Wenjie; Li, Quanfeng; Dong, You
Abstract: In order to evaluate the shear lag effect of high strength steel (HSS)-Ultra high performance concrete (UHPC) composite beams with perfobond strip connectors (PBLs), this study involved the preparing and testing of six HSS-UHPC composite beams with different shear connections, deck width-to-thickness ratios, and deck width-to-span ratios. Failure mode, load-deflection curve, load-slip response, and stresses distribution of the HSS-UHPC composite beams were presented and discussed. Experimental results indicated that uniform elastic stresses in the UHPC deck cross-section were observed, and the stress distribution became uneven as the composite beam entered the plastic stage. Under a load of 0.3 M u, the bending stress at the cross-section top center of UHPC deck was 5.3% larger than that at the edges, and this stress discrepancy went up to 9.4% as load approached 0.9 M u . To gain insight into the plastic performance of the tested beams, the finite element (FE) model was further established for the composite beams. Numerical results indicated that the sectional stress hysteresis coefficient ( λ ) at L/4 near loading point was briefly similar to that of the mid-span in elastic stage, and the stress unevenness increased as the shear connection degree dropped. As the connection degree decreassed from 1.02 to 0.89 and 0.76, the λ of the investigated beams were magnified by 2.7% and 6.7%, respectively. Results also showed that the shear lag effects degraded as deck width-to-thickness ratio increased. The λ for the beams using width-to-thickness ratios of 4.50 and 4.09 were 13.3% and 18.6%, both smaller than that using the ratio of 5.63. Moreover, as the width-to-span ratio increased from 0.20 and 0.24, the stress hysteresis effect of HSS-UHPC composite beams barely varied. Highlights: Structural behavior of HSS-UHPC composite beam is studied by a bending test. Lateral distribution of normal stresses in UHPC slab of the composite beam is analyzed. Shear lag effect of HSS-UHPC composite beam under flexural loading is explored. Critical design parameter affecting shear lag effect of the composite beam is assessed.